The amorphous interphase formed in an intermetallic-free Cu/Sn couple during early stage electromigration. (October 2018) - Liang, Chien-Lung; Lin, Kwang-Lung
Abstract: The early stage athermal electromigration behavior at the heterogeneous interface of a Cu/Sn couple was investigated at room temperature. The material interaction formed an interphase consisting of an amorphous Cu-Sn matrix, enriched with Cu (87.6–93.4 at.% Cu) and embedded with a few nano-crystalline Cu cells. The Cu-rich characteristic of the interphase indicates atypical interdiffusion behavior. The formation of the interphase was governed by the electrodisruption of the cathode Cu lattices accompanying the interdiffusion between Cu and Sn atoms. The occurrence of the meta-stable interphase is believed to be a preliminary stage prior to the subsequent intermetallic formation. Graphical abstract: Unlabelled Image